Building a motivation scale for young volleyball players aged (17-19) years - raad, ayad; Hakmit , Asmaa (Journal of Physical Education, 2023)
The research aimed to build a motivation scale for young volleyball players aged (17-19) years. the researchers used the descriptive survey method, and the research subject was selected from young volleyball players ages 17-19 years. The scientific roles were applied to approve the Validity and reliability of the scale. the researchers recommend the scale be used for different players in order to identify their motivation to enable them to reach the highest levels.